HEALTH STATUS AND DEMOGRAPHIC PROCESSES OF THE POPULATION OF THE REPUBLIC OF TYVA AT THE BEGINNING OF THE XXI CENTURY - Эрдыниева, Людмила Салчаковна (Medicine in Kuzbass, 2023)
The purpose of the study is to assess the state of health and demographic processes in the Republic of Tyva at the beginning of the XXI century.Materials and methods. The paper uses analytical and statistical research methods, including component analysis and T. Greville I and II methods.Results. The main trends of the modern development of the demographic situation of morbidity and mortality in the Republic of Tyva are revealed.Conclusion. In the Republic of Tyva, the dynamics of the number is contradictory: the reduction in the number in the early 90s was replaced by its growth. There has been an increase in the urban population due to the migration of the rural population to the city. The aging process of the population has begun to develop in the republic. The average life expectancy is significantly lower than in Eastern Siberia and in the Russian Federation. The Republic of Tyva has one of the highest mortality rates in the country from infectious and parasitic diseases, respiratory diseases and infrequent cases. In recent years, there has been a reduction in the overall mortality rate, as well as an increase in the average life expectancy. Mortality (morbidity) from «controlled» causes is high, that is, the contribution from which can be reduced due to the impact of social policy measures.
Keywords: medical and demographic indicators; birth rate; mortality; morbidity; average life expectancy of SPP; Republic of Tyva; Russian Federation